Penggunaan Media Audio Visual untuk Menguatkan Daya Ingat tentang Asmaul Husna - Fauziah, Hisni; Asep Nugraha, Sopian (Diksi: Jurnal Pendidikan dan Literasi, 2025)
Memory skills in early childhood need to be stimulated, as this memory ability is one of the cognitive abilities that children need to develop. So, one way to strengthen early childhood memory is through audio-visual media. The purpose of this study is to investigate the ability to recall early childhood memories in Kober Al-Istiqomah after being exposed to audio-visual media. This study employs a qualitative descriptive research method. The population of this study consists of all Kober Al Istiqomah students, totalling 10 individuals. The research sample was 5 people. The instruments of this research are interviews and observations. The results of the study indicate that the use of visual media can be an effective approach to enhancing the memory of Asmaul Husna in early childhood